1986
DOI: 10.1037/h0080086
|View full text |Cite
|
Sign up to set email alerts
|

The effect of testing on the forgetting of related and unrelated associates.

Abstract: Separate groups of subjects studied lists of word pairs in which the members of the pairs were either unrelated or strong or weak associates. A single study trial was given. In addition, one group received three study presentations on the unrelated list. An immediate cued recall test for half of the pairs was followed by a second test on all pairs either 10 min, 48 hr, or 1 week later. The associated pairs, both strong and weak, were forgotten less rapidly than the nonassociated pairs, but the effect was large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 8 publications
6
40
1
Order By: Relevance
“…The reconstruction or effort hypotheses are also consistent with views that retrieval operations strengthen the memory trace (Runquist, 1983(Runquist, , 1986). Runquist reported that the slope of the forgetting curve was reduced more for items receiving an initial test than for those not receiving an initial test.…”
Section: The Spacing Effect In Children 441supporting
confidence: 70%
“…The reconstruction or effort hypotheses are also consistent with views that retrieval operations strengthen the memory trace (Runquist, 1983(Runquist, , 1986). Runquist reported that the slope of the forgetting curve was reduced more for items receiving an initial test than for those not receiving an initial test.…”
Section: The Spacing Effect In Children 441supporting
confidence: 70%
“…Other studies have looked at cued recall tasks, with final tests delayed by days (Raffel, 1934;Runquist, 1986aRunquist, , 1986bRunquist, , 1987 or weeks (Runquist, 1983;Spitzer, 1939). However, these studies did not compare retention of items in a test condition with retention of items in a restudy condition.…”
Section: The Present Studymentioning
confidence: 99%
“…As such, it is possible that any apparent differences in the rate of forgetting reflected differences in the amount of overall exposure time rather than the effects of testing. Furthermore, in some studies (Runquist, 1983(Runquist, , 1986b, final test accuracy in the no-test control condition was assessed as a proportion of all items in that condition, whereas final test accuracy in the test condition was assessed on the basis of the number of items successfully recalled on the intervening test. Thus, the rate of forgetting in the no-test condition was assessed for all items, whereas the rate of forgetting in the test condition was assessed only for the easier and/or initially better-learned items.…”
Section: The Present Studymentioning
confidence: 99%
“…It is possible thatany mnemonic effects of a memory test are simply due to this representation of the target material and not to the memory retrieval itself (as suggested by Skaggs, 1920). Obviously, this criticism applies to those studies that have shown that receiving a memory test is better for later retention than simply having an equivalent amount of free time (Bartlett, 1977;Bartlett & Tulving, 1974;Darley & Murdock, 1971;Madigan & McCabe, 1971;McDaniel, Kowitz, & Dunay, 1989;Modigliani, 1976;Runquist, 1983Runquist, , 1986Young, 1971). Whether there is an active, mnemonic effect of retrieval has important theoretical implications.…”
mentioning
confidence: 93%